Digital Literacy and Intrinsic Motivation of High-Achieving Students in Chemistry Learning at Senior High School - Saputri, Utari Aulia Tianda; Siregar, Anggi Desviana; Saslina, Tri (Jurnal Inovasi Pembelajaran Kimia, 2025)
This study examines the digital literacy and intrinsic motivation of high-achieving chemistry students at SMA Negeri 1 Kerinci in the 2024/2025 academic year, and explores the relationship between these variables. The sample comprised science program students who participated in the National Science Olympiad (KSN). Using a mixed-methods sequential explanatory design, quantitative data were collected through questionnaires based on six digital literacy indicators and three intrinsic motivation indicators, followed by structured interviews for qualitative insights. Results showed that students demonstrated high digital literacy in “Uses to Produce Original Work” and “Considers Source,” but lower performance in “Selects.” Their intrinsic motivation was also high, particularly in learning activity, perseverance, and exam resilience. The Pearson correlation test indicated a significant positive relationship between digital literacy and intrinsic motivation (r = 0.679, p < 0.05), suggesting that improved digital literacy enhances students’ internal drive to learn. Overall, the findings underscore the need to integrate digital literacy into chemistry learning strategies to foster greater motivation and holistic academic achievement among students.